Essays on renewable energy communities - Soeiro, Susana Teixeira (2022)
Environmental and economic trends of the last decades have forced the world to urgently rethink current energy markets and energy supply. Thus, a deeper study on Renewable Energy Communities (REC) is a recent and emerging concern due to their relevant role in some energy markets and, in some cases, their key role in the future. This new generation of citizen intervention presents itself to democratize the energy sector in all its phases, from production to supply. Community energy represents a legal form of business present throughout the world and throughout the economy, namely in agriculture, finance, general consumption, and industrial production, albeit on a smaller scale. According to the Cooperative Alliance (ICA), the definition is clear. The objectives of this business model are to increase member participation and governance to a new level; position community energy as sustainability builders, build the community energy message and ensure community identity, ensure legal structures to support community growth and secure reliable community capital, ensure member control. It is often argued that laws and regulations raise various restrictions on REC. Therefore, renewable energy development should be supported by public policy, in all European countries. The development of REC’s does not appear to be the same in all member states. Moreover, its development even seems to be different, and depending on the European country. In Southern European countries, which do not have a tradition of green energy dissemination, show a lower development of REC’s. So, through a questionnaire addressed to participants in REC’s and a questionnaire addressed to the general population, it is intended to study and better understand what citizens' energy initiatives are, their main characteristics, benefits, barriers, and the motivations of individuals who participate in them. Citizen participation is a crucial point for the development of communities. The main motivation for participation seems to be concern about environmental and climate impacts. We also observe that, in these communities, trust is pointed out as important for the development of any RE project. As for the benefits, the results lead to significant insights: firstly, it is mentioned by the survey participants that the environmental benefits outweigh the financial ones when creating and developing REC’s. Secondly, it is significant to highlight that the benefits and impacts that RECs bring to the regions where they are created are perceived as essential. On the barriers, environmental policies and costs are among the barriers that are most pointed out to the adoption and development of REC’s. Finally, it has been shown that there is a disparity between the countries of Southern Europe and those of Northern Europe, this difference being justified by economic and environmental factors and the legislative framework. In short, REC’s are significant for the energy transition and should be supported by European governments and by national and European policies.